Pelestarian Kesenian Islam Melalui Pendidikan Non Formal (Studi Kasus di Taman Pendidikan Al-Qur'an (TPA) Nasrullah Kertosobo, Bukuran, Kalijambe Tahun Pelajaran 2016/2017) - Thayibah, Khamsah Ruhana, Dra. Chusniatun, M.Ag (2017)
Art is a sense of beauty inherent in every human being and can be expressed through many ways. Furthermore, art can be used as a means, including Islamic arts. Islamic art is an art containing Islamic values. It can be used as a means of da'wah amar ma'ruf nahi munkar (enjoining what is right, forbidding what is wrong), delivering Islamic values contained in the Holy Koran in order to be easily accepted in the various lines. Therefore, all parties need to make some efforts to preserve it. The research has aimed to describe Islamic art preservation through non formal education in TPA Nasrullah Kertosobo, Bukuran, Kalijambe. The research was a kind of field research by using descriptive qualitative approach. The research was conducted from December 28th, 2016 till January 11st, 2017 in TPA Nasrullah Kertosobo, Bukuran, Kalijambe. The collecting data used interview, observation, and documentation. The method of analyzing data used descriptive qualitative analysis, not by number but narration/ words through collecting data, data reduction, and data display. Moreover, the conclusion was conducted by using deductive method, way of thinking that departed from theory, then matched with the data. According to the data analysis, it can be concluded that Islamic art preserved by non formal education in TPA Nasrullah divided into vocal art, music art and fine art. Vocal art was preserved through Shalawat Ratib Al-Hadad. Music art was preserved through hadrah. Fine art was preserved by kaligrafi.